How to prioritize allocating conservation efforts: an alternative method tested with imperilled herpetofauna. (17th June 2015) - Kacoliris, F. P.; Velasco, M. A.; Berkunsky, I.; Celsi, C. E.; Williams, J. D.; Di‐Pietro, D.; Rosset, S.
Abstract: Several methods were developed with the aim of prioritizing conservation efforts. However, most of these methods were focused on ranking areas for land protection, without offering alternatives for sites poorly ranked. We propose an alternative method that allows prioritizing conservation efforts independently of the status of a specific area. The conservation priorities method considers data related with biodiversity, availability of suitable habitat and human pressure, on area‐based units. This information is then standardized, obtaining a vector of three values, which reflects the situation of a specific area categorically (positive and negative) and quantitatively (how far from zero). Based on these values, specific conservation efforts can be settled at each area‐based unit. We tested this methodology on several political units located at the Pampean Coastal Dunes in Argentina, using herpetofauna as surrogate taxon. Our results confirm the needs of performing several conservation approaches to deal with Pampean Coastal Dunes' problems. The conservation priorities method showed to be a useful tool to characterize sites and to set conservation efforts based on its specific status, supplementing current methodologies.